Designing a Field Service Management Application Using the Double Diamond Approach: A Usability Evaluation Study - Arin, Ikrar Adinata; Murad, Dina Fitria; Warnars, Harco Leslie Hendric Spits; Meyliana, . (Engineering, Technology & Applied Science Research, 2025)
Field Service Management (FSM) applications play an essential role in modern service operations, but many existing solutions have not effectively addressed the complex needs of field technicians. This study presents a systematic approach to designing and evaluating FSM applications using the Double Diamond methodology integrated with Digital Twin technology, applying a four-phase design process: Discover (field observation and interviews), Define (analysis of requirements and problem formulation), Develop (iterative prototyping with Digital Twin integration), and Deliver (implementation and usability evaluation). The evaluation involved 15 field technicians from three telecommunications service providers using the System Usability Scale (SUS) method. The results showed an average SUS score of 72.33, which falls into "good", with variations between service providers (technicians from service provider C provided the highest score of 89.5, and those from A and B provided 76.5 and 51.0, respectively). The item analysis showed that ease of use, frequency, and integration of functions had the highest scores. This study presents the first systematic application of the Double Diamond method to a Digital Twin-based FSM design, providing empirical evidence of its effectiveness through a comprehensive usability evaluation.